CONNECTING MINDS AND SCREENS: THE MEDIATING INFLUENCE OF CYBERLOAFING ON COGNITIVE ABSORPTION AND SOCIAL WELL-BEING - Elrisfa Magistarina; Rahayu Hardianti Utami; Rizal Kurniawan; Dedi Supendra; Verlanda Yuca; Putri Anisa; Altashya Nurul Budiani; Yonatri Cahya Ningtias (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2024)
Social well-being is a part of subjective well-being used to measure mental health as a measurement of mental health, which is an indicator of quality of life. People can achieve social well-being when they have a good and deep quality relationship with others. However, people use technology almost daily, impairing their social well-being. Moreover, they also tend to do cyberloafing, which makes them spend more time on their gadget. This project's principal objective was to investigate cyberloafing's effect on cognitive absorption and social well-being. A quantitative method using three questionnaires (cognitive absorption scale, cyberloafing questionnaire, and social well-being) involving 178 respondents was employed. The data was analyzed using Mediation Analysis in JASP software. The findings indicated a partial mediation in cyberloafing on the relationship between cognitive absorption and cyberloafing.